Immunization - Must Be Safe or We Will All Be Sorry - Greg Hammond (Canadian Journal of Infectious Diseases)
Immunization programs are among the most effective of all health care interventions, and they are among the few that are potentially cost-saving. However, concerns about immunization safety appear to be increasing, despite technological developments that have created safer vaccines than ever before and despite the solid scientific evidence of the safety of current immunization programs. This is due in part to the success of immunization programs, where major advances in immunization have caused the virtual disappearance of many common communicable diseases. This has resulted in the perception by some individuals that adverse events, which occasionally follow immunization, are now more common and potentially more of a hazard than the diseases for which the immunizations were developed.